Strategi Badan Siber dan Sandi Negara (BSSN) Dalam Menghadapi Ancaman Siber di Indonesia - Sudarmadi, Damar Apri; Runturambi, Arthur Josias Simon (Jurnal Kajian Stratejik Ketahanan Nasional, 2019)
Cybersecurity governance in Indonesia is still partial and sectoral, resulting in the handling of cybersecurity problems not yet integrated. This makes cyber threats even more real, especially when linked to threats to cybersecurity for government and private institutions. Therefore, cybersecurity management must be carried out in an integrated manner to prevent cyber threats in all aspects of national and state life. In 2017, the National Cyber and Crypto Agency (BSSN) was formed based on the Presidential Regulation on BSSN which states that BSSN is tasked with implementing cyber security effectively and efficiently by utilizing, developing and consolidating all parties related to cybersecurity. The establishment of the BSSN considers that the cybersecurity sector is one of the areas in government that must be strengthened and encouraged in order to realize national security, increase economic growth, ensure the implementation of government policies and programs in the cybersecurity sector. BSSN was formed based on urgent needs in the midst of various challenges and problems related to the implementation of cybersecurity and encryption. BSSN is a government institution that is under and responsible to the President. The formation of BSSN is expected to be able to face problems and challenges in the present and future cyber era. This research is a descriptive type of research using a qualitative approach that seeks to explain the strategy of the National Cyber and Crypto Agency (BSSN) to increase commitment in the field of cybersecurity in dealing with cyber threats in Indonesia.